Pemanfaataan Mikroalga Sebagai Perbaikan Ekosistem Air Akibat Limbah Cair Ampas Tahu - Mohammad Fathoni Hakim; Juniar Tri Wardana; Maulana Ja'far Shidiq; Muhammad Assegaf; Denny Oktavina Radianto (Universitas Pahlawan Tuanku Tambusai, 2024)
The increase in population in Indonesia is directly proportional to existing economic activities. The main need that every human needs is food, so many food industries continue to develop. One of these industries is the tofu making industry. Many of these industries result in several problems such as unpleasant odors from waste and damage to the water ecosystem in rivers. On the other hand, the use of microalgae is still often considered inadequate, so innovation needs to be carried out to optimize the usefulness of microalgae. Therefore, researchers made an innovation by using microalgae to remove COD and eliminate bad odors in tofu dregs liquid waste. This research method is an experiment using data from journals and the internet. Data processing is descriptive in the form of data results that are compared with materials used every day